2014
DOI: 10.1016/j.eurpolymj.2014.01.034
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a spin-crossover Fe(II)-1,2,4-triazole polymer complex gel in toluene. Small angle neutron scattering and viscoelastic studies

Abstract: In this paper we report the study of metallo-organic polymer gels of [Fe(II) (4-octadecyl-1,2,4-triazole) 3 (ClO 4 ) 2 ] n in toluene. A thorough investigation of the molecular structure and the viscoelastic properties of the metallo-organic polymer gels in toluene has been carried out by small angle neutron scattering and controlled stress oscillatory rheology as a function of temperature and concentration in order to understand the selfassembly process leading to the gel formation. The results obtained point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…The gelation process is considered to be a hierarchical assembly that usually follows the subsequent steps: 1) dimerization of two individual molecules, 2) oligomer formation by interaction of dimers with further molecules, 3) formation of polymer fibrils, 4) fiber formation by bundling of fibrils, 5) interaction of fibers to give an infinite, interconnected network along the entire sample and 6) immobilization of the solvent by the fiber network. [103,104] Although several examples of SCO gels have been reported in the literature, [46,70,[104][105][106][107][108][109][110][111][112][113][114] it is noteworthy that mostly Fe(II)-triazole complexes containing long or bulky aliphatic ligands or counter-anions were reported to form gels. It is commonly assumed that these types of compounds are efficient gelators due to lipophilic interactions between the aliphatic part of the SCO complexes and the chosen solvents.…”
Section: Sco Gelsmentioning
confidence: 99%
See 2 more Smart Citations
“…The gelation process is considered to be a hierarchical assembly that usually follows the subsequent steps: 1) dimerization of two individual molecules, 2) oligomer formation by interaction of dimers with further molecules, 3) formation of polymer fibrils, 4) fiber formation by bundling of fibrils, 5) interaction of fibers to give an infinite, interconnected network along the entire sample and 6) immobilization of the solvent by the fiber network. [103,104] Although several examples of SCO gels have been reported in the literature, [46,70,[104][105][106][107][108][109][110][111][112][113][114] it is noteworthy that mostly Fe(II)-triazole complexes containing long or bulky aliphatic ligands or counter-anions were reported to form gels. It is commonly assumed that these types of compounds are efficient gelators due to lipophilic interactions between the aliphatic part of the SCO complexes and the chosen solvents.…”
Section: Sco Gelsmentioning
confidence: 99%
“…The complex [Fe(ODT)3] 2+ , with various counter-anions, is probably the most deeply investigated compound capable to form gels in different solvents. [87,[109][110][111] The group of López et al studied the physical properties of the corresponding perchlorate complex. [109] They observed that the gel formed in toluene consists of rod-like structures that are randomly oriented.…”
Section: Sco Gelsmentioning
confidence: 99%
See 1 more Smart Citation
“…For certain applications, a specific spatial arrangement is crucial. Research performed over the last decades proposed the preparation of SCO materials as thin-films [9,10], liquid crystals [11], and as supramolecular gels [12,13]. In order to overcome this problem, in our previous study, electrospun fibers of blends of the [Fe(II) (4-octadecyl-1,2,4-triazole) 3 (ClO 4 ) 2 ] n metallo-organic polymer and atactic polystyrene were developed.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to that work, we reported the development of [Fe(II) (4-octadecyl-1,2,4-triazole) 3 (ClO 4 ) 2 ] n metallo-organic polymer gel and the effect of the solvent on the gelation properties [15]. We demonstrated, by means of Small Angle Neutron Scattering (SANS) and rheology, that the responsibility for the gelation is with the side-by-side aggregation into fibers of the individual metallo-organic polymer chains [13]. The formation of hybrid thermo-reversible gels from organic and metallo-organic polymers is also postulated as an interesting technological alternative.…”
Section: Introductionmentioning
confidence: 99%